L’invention de l’enfance : modalités institutionnelles et support idéologique - Laberge, Danielle (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
Today's social status of children is the result of social, economic and cultural changes that have characterized western societies all through the 19th century. The establishment of this particular status came during a movement of general differentiation that affects all the practices of delinquents. The present analysis solely concerns the United States and in particular examines the emergence of three institutions intended exclusively for child care : reform school or refuge, family placement and compulsory school attendance.